Can insider power affect employment? - Pilar Díaz-Vázquez; Dennis J. Snower (German economic review, 2003)
Do firms reduce employment when their insiders (established, incumbent employees) claim higher wages? The conventional answer in the theoretical literature is that insider power has no influence on employment, provided that the newly hired employees (entrants) receive their reservation wages. The reason given is that an increase in insider wages gives rise to a countervailing fall in reservation wages, leaving the present value of wage costs unchanged. Our analysis contradicts this conventional answer. We show that, in the context of a stochastic model of the labor market, an increase in insider wages promotes firing in recessions, while leaving hiring in booms unchanged. Thereby insider power reduces average employment.
Keywords: J21; J23; J31; J32; J33; 330; Employment; Wage determination; market power; insiders; hiring and firing costs; Lohnstruktur; Insider-Outsider-Modell; Arbeitsuche; Anspruchslohn; Marktmacht; Theorie